Electric-current-induced thermal stress around a non-circular rigid inclusion in a two-dimensional nonlinear thermoelectric material - Yang, Hai-Bing; Yu, Chuan-Bin; Tang, Jie-Yao; Qiu, Jian; Zhang, Xiao-Qing (Acta mechanica, 2020)
The plane problem of a non-circular rigid inhomogeneity embedded in an infinite thermoelectric matrix under a uniform remote electric current is investigated based on the complex variable method. The inclusion is assumed to be electrically insulated and thermally conductive. Techniques of Faber and Fourier series are used to solve the corresponding boundary value problems. The obtained results show that the shape, bluntness and heat conductivity of the inclusion have a significant effect on the interfacial thermal stress distribution induced by the external electric current. In addition, the Von Mises stress concentration around a non-circular inclusion could be lower than that around a circular inclusion by designing the shape and orientation of the inclusion properly.